Liquid retail: cultural perspectives on marketplace transformation. Issue 5 (3rd September 2018) - Kervenoael, Ronan de; Bajde, Domen; Schwob, Alexandre
ABSTRACT: Inspired by Bauman's notion of "liquidity, " we problematize the socio-cultural dynamics taking place in contemporary retail. The notion of liquid retail enables researchers to untangle marketplace transformation and to highlight developments centred around markets and market-actors that jointly transform each other. This introduction underlines, as a point of departure, recent developments in retailing that have been marked by the corrosion of fixity and boundaries. We provide a short synopsis of marketplace transformation and liquid retail, from a socio-cultural perspective, and summarize the papers included in this special issue.